Roadside memorials in contemporary Russia: folk origins and global trends - Yudkina, Anna (Religion and society in Central and Eastern Europe, 2014)
In this paper we consider new forms of memorialization - roadside memorials - in contemporary Russia which are similar to traditional forms functionally and pragmatically, but which have new dimensions at the same time. The roadside memorials at the places of sudden tragic deaths in urban and suburban environments reflect both individual and public contexts. This paper is based on our 2010-2013 field work in Tula and Vladimir Regions, also it includes a number of particular cases from another regions of Russia. During the field work we had observed 138 roadside memorials in 2010 and about 40 in the next years. We use the results of 37 interviews with people, involved in to the practice of spontaneous memorialization, undertakers, professional drivers, Orthodox priests. traffic police officers, road servicemen and local authorities. Finally we use the results of internet survey about the attitude towards roadside memorials, which include 80 respondents. Our main hypothesis states that Russian spontaneous memorials in general and roadside memorials particularly are less explicit and emphasize the performative or societal protest side of the practice. Mostly the construction of roadside memorials are a sign of transformation of mourning rituals in Russia from taking place only in institutionalized official place to taking place also in individualized spatial place. In this paper we consider new forms of memorialization - roadside memorials - in contemporary Russia which are similar to traditional forms functionally and pragmatically, but which have new dimensions at the same time. The roadside memorials at the places of sudden tragic deaths in urban and suburban environments reflect both individual and public contexts. This paper is based on our 2010-2013 field work in Tula and Vladimir Regions, also it includes a number of particular cases from another regions of Russia. During the field work we had observed 138 roadside memorials in 2010 and about 40 in the next years. We use the results of 37 interviews with people, involved in to the practice of spontaneous memorialization, undertakers, professional drivers, Orthodox priests. traffic police officers, road servicemen and local authorities. Finally we use the results of internet survey about the attitude towards roadside memorials, which include 80 respondents. Our main hypothesis states that Russian spontaneous memorials in general and roadside memorials particularly are less explicit and emphasize the performative or societal protest side of the practice. Mostly the construction of roadside memorials are a sign of transformation of mourning rituals in Russia from taking place only in institutionalized official place to taking place also in individualized spatial place.